International Marketing / Third Edition - Terpstra Vern (The Dryden Press, 1983)
The International Environment, Introduction to International Marketing, The Political-Legal Environment, International Marketing Management, Marketing to the World, Distribution: Entering Foreign Markets, Pricing in International Marketing, Coordinating International Marketing, International Marketing Planning, Organization and Control of International Marketing, Supplementary Cases, Index.
The International Environment, Introduction to International Marketing, The Political-Legal Environment, International Marketing Management, Marketing to the World, Distribution: Entering Foreign Markets, Pricing in International Marketing, Coordinating International Marketing, International Marketing Planning, Organization and Control of International Marketing, Supplementary Cases, Index.